2005
DOI: 10.1002/app.22119
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of a dispersant for gypsum paste from acid hydrolysis lignin

Abstract: ABSTRACT:The preparation of dispersants with carboxyl groups from acid lignin (a byproduct in the saccharification process of woody materials that are renewable resources) was investigated, and their dispersion efficiency was evaluated. In this study, sulfuric acid lignin (SAL) was selected as a representative acid lignin. To convert SAL to water-soluble polymers, it was first subjected to phenolation with sulfuric acid to enhance its chemical reactivity. The introduction of a carboxy group was carried out wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Similarly, an increase in peak intensity at 1600, 1263 and 1030 cm -1 corresponds to the introduction of carboxylate group at the para position of aromatic rings in the modified lignin [18]. Thus, FTIR results confirm that there was an introduction of carboxylate group to the modified lignin due to the carboxymethylation of lignin with sodium chloroacetate.…”
Section: Ftir Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…Similarly, an increase in peak intensity at 1600, 1263 and 1030 cm -1 corresponds to the introduction of carboxylate group at the para position of aromatic rings in the modified lignin [18]. Thus, FTIR results confirm that there was an introduction of carboxylate group to the modified lignin due to the carboxymethylation of lignin with sodium chloroacetate.…”
Section: Ftir Analysissupporting
confidence: 78%
“…Straw soda aqueous lignin was also modified to form chelating resins for binding to copper metals [17]. In another report, an acetone-based lignin model compound was carboxymethylated using bromoacetic acid to prepare carboxymethylated lignin, which was also used as dispersant for gypsum paste [18].…”
Section: Introductionmentioning
confidence: 99%
“…SLs are by-product of sulfite cellulose pulp production, they contain hydrophilic groups which make them water soluble (Dawy et al 1998;Telysheva et al 2001;Wang 2002). They can be described as anionic surfactants, which are relatively low cost and are widely used in many applications (Li et al 2007;Matsushita et al 2005;Pei et al 2008;Gogoi 2009). Studies have shown that aqueous solution of SL could reduce the IFT between oil and water thereby releasing the captured oil blobs from the porous media (Son et al 1982;Hornof et al 1982;Babu et al 1984;Gogoi 2010).…”
Section: Methodsmentioning
confidence: 99%
“…An optimal lignin management is part of this strategy. Acid lignin is, for example, generated as a by-product of bioethanol production using acid saccharification of woody biomass (Matsushita et al 2005 ;Da Silva et al 2011 ;Cerrutti et al 2012 ). There is a large amount alkali lignin (AL) available in the waste liquor of soda pulping .…”
Section: Introductionmentioning
confidence: 99%